To find the equation of the dotted graph, which is a reflection of the solid graph \( f(x) = x^3 + 1 \) across the x-axis, you need to negate the output of the function.
The reflection across the x-axis would mean that if \( f(x) = y \), then the reflected graph would be \( g(x) = -y \).
So, apply this to the equation:
-
Start with the original function: \[ f(x) = x^3 + 1 \]
-
Reflect it across the x-axis: \[ g(x) = -(x^3 + 1) = -x^3 - 1 \]
Thus, the equation of the dotted graph is \( g(x) = -x^3 - 1 \).
Therefore, the answer is Option #2.